The Ser680Asn polymorphism in the follicle‐stimulating hormone receptor gene is associated with the ovarian response in controlled ovarian hyperstimulation. (3rd October 2014) - Huang, Xianliang; Li, Lu; Hong, Ling; Zhou, Weijin; Shi, Huijuan; Zhang, Huiqin; Zhang, Zhaofeng; Sun, Xiaoxi; Du, Jing
Summary Objective Polymorphisms in the follicle‐stimulating hormone receptor (FSHR) gene are reported to be associated with the ovarian response in controlled ovarian hyperstimulation (COH), although there remains some discordance between studies. Here, using the largest patient sample to date, we evaluated the association of the p.Ser680Asn (S680N) polymorphism in the FSHR gene with the outcome of COH. Design Cohort study. Setting Medical academy and hospital. Patients A total of 1250 infertile Chinese women undergoing IVF/ICIS‐ET treatment were included. Measures The association between an FSHR polymorphism (S680N) and the ovarian response was analysed. Genotyping was performed by utilizing direct sequencing and the Sequenom MassARRAY iPLEX platform. Follicular fluid oestradiol (E2) and follicle‐stimulating hormone (FSH) concentrations were determined using electrochemiluminesence immunoassays. The ovarian response parameters were analysed based on the FSHR genotypes. The odds ratios (ORs) and 95% confidence intervals (95% CIs) were calculated for the risk genotypes and alleles. Results There were linear correlations between the basal FSH level, exogenous gonadotropin consumption, and oocytes retrieved and the Ser680 alleles. Patients in the homozygous SS group demonstrated higher basal FSH levels, required more dosage of exogenous gonadotropin for ovarian stimulation, and had fewer numbers of oocytes retrieved compared with patients in the homozygous NN and heterozygous groups. Logistic regression analysis revealed that the OR of a poor ovarian response for the NS genotype was 1·79 (95% CI 1·28–2·61; P < 0·001), whereas that for the SS genotype was 2·25 (95% CI 1·40–3·58; P < 0·001) after adjusting for age, BMI and basal FSH level. The concentration of E2 in the follicular fluid was significantly higher in subjects with the NN genotype than the SS genotype (772 ± 545 ng/ml vs. 1299 ± 504 ng/ml). Conclusions Follicle‐stimulating hormone receptor gene polymorphism at position 680 is associated with different ovarian responses to controlled ovarian hyperstimulation.